Empowering Entrepreneurs for Success in The Post-Covid-19 World of Micro, Small, and Medium-Sized Businesses - Darmo, Ika Suhartanti (UNIVERSITAS PGRI YOGYAKARTA, 2022)
AbstractThe SEMASA Serpong women entrepreneurs have seen their earnings take a hit because to the Covid 19 pandemic. This community service project seeks to help the SEMASA Serpong women entrepreneurs get back to work after the Covid-19 pandemic by improving their business acumen and guiding them through the steps of getting their own Business Registration Numbers and Micro Small Business Permits. There was evidence that the SEMASA Serpong women entrepreneurs gained a higher level of competency as a result of this exercise. Making financial reports effectively allowed them to more easily keep tabs on the company's financial standing, understand the weaknesses and strengths of corporate finance, and plan for the expansion of the business in the future. Having a solid and well-organized financial report allows them to apply for and get loan capital from banks and cooperatives, allowing them to expand their business. The SEMASA Serpong women entrepreneurs gained confidence and redoubled their efforts to grow their enterprises after receiving guidance with obtaining the Business Registration Number and Micro Small Business Permit, which are necessary for the legal functioning of their enterprises. The post-test score of 96.86% is considerably higher than the pre-test score of 0.83%, demonstrating considerable improvement in knowledge and skill. These findings provide valuable information for the BINUS University Team to use in its efforts to empower the SEMASA Serpong women entrepreneurs so that they may continue to build their businesses and provide for their families.Keywords: Empowering Entrepreneurs, Covid-19